Time On Florida's Death Row: A Theory Of Benign Neglect - Willis, Angela (2008)
This thesis attempts to identify and explain what influences the length of time an inmate spends on Florida's death row. A systematic random sample of 33 Florida death row inmates was drawn from the Florida Department of Corrections death row roster and the Florida Commission on Capital Cases inmate roster. Documented for each death row inmate was how long he spent on Florida's death row navigating the various stages and steps in Florida's post-conviction capital punishment process. The data show that petitions to the state trial courts and appeals to the Florida Supreme Court take the longest time in Florida's post-conviction capital punishment process. It also shows a considerable amount of dead time, which refers to any additional time that an inmate spends on death row with no legal actions pending. A theory of benign neglect is proposed as the most likely explanation for the excessive delays